The Development of Student Worksheets (LKPD) with Environmental Care Character Content in Science Learning in Grade IV: Pengembangan Lembar Kerja Peserta Didik (LKPD) dengan Muatan Karakter Peduli Lingkungan Pada Pembelajaran IPA di kelas IV - Heni Mukti Asih Maisari S; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to develop LKPD with environmental care content. LKPD is integrated with the concept of environmental care in the hope of forming students' environmental care attitudes. In addition, this study also measured the feasibility and user responses, namely teachers and students of SDN 08 Lubuklinggau. This research is a research and development with a 4D model. The object of the research is LKPD with the content of being ready to care for the environment. The research stages consist of four stages, namely define, design, develop and disseminate. The instruments used are a feasibility test questionnaire, interview guidelines, and student response questionnaires. The feasibility test was carried out by 6 validators, namely 2 Material Experts, 2 Language Experts and 2 Display Experts. User response test was conducted on 21 fourth grade students of SDN 08 Lubuklinggau . Data analysis used percentage technique and processed descriptively. The results of the LKPD feasibility test with environmental care content by the validator in terms of the front page, table of contents, study instructions, material feasibility, language presentation, and display feasibility, material feasibility obtained 0.75 with appropriate criteria, language feasibility result 0.80 with very feasible criteria and the results of the feasibility display 0.87. The results of the LKPD field test with environmental care content, obtained a positive response given by the teacher through interviews and 85,90 by students with quite positive criteria. Based on the results of the feasibility test and user responses, the LKPD developed is feasible and positive to use.